2020
DOI: 10.4236/ojmn.2020.102029
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Use of Dopamine Agonist in Controlling the Residual Mass in Non Functioning Pituitary Adenoma

Abstract: Background: Non-functioning pituitary adenoma (NFPA) is a challenging tumor. It is usually reached to a large size before it is clinically manifested. Operative interference is the first option in treatment of large NFPA causing compressive manifestations but with frequent postoperative residual masses that is usually required additional treatment. Postoperative radiotherapy carried frequent side effects which open the door for postoperative medical treatment with dopamine agonist (DA) drugs based on the fact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…In agreement with our findings, the study of Mahmoud et al, [19] reported that 32-cases were involved in this work. 21-cases (66%) were women and 11-cases (34%) were men.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In agreement with our findings, the study of Mahmoud et al, [19] reported that 32-cases were involved in this work. 21-cases (66%) were women and 11-cases (34%) were men.…”
Section: Discussionsupporting
confidence: 94%
“…D2R and estrogen receptors [ER a (ESR1)] and ERP (ESR2) had been immuno-stained, digitalized, and counted on the Cedars-Sinai Translational Research Core in 53 tumour specimens of DAmanaged cases. The percent of positive cells and staining intensities was recorded for all slides via the immuno-reactivity score system (IRS) [15] and the (QUICK-Score) method [19] .…”
Section: Immuno-histo-chemistry (Ihc)mentioning
confidence: 99%